«Fiz este libro en que puse algunas cosas que fallé en un libro»: il Libro del cavallero et del escudero di Juan Manuel e il Llibre de l’orde de cavalleria di Ramon Llull. - Luongo, Salvatore (Scripta, 2022)
The identification, starting from Francisco de Paula Canalejas, of Ramon Llull’s Llibre de l’orde de cavalleria as a possible source of Juan Manuel’s Libro del cavallero et del escudero has originated a lively debate on the degree of autonomy of the Manueline treatise. That the «libro» in which don Juan «falló» «algunas cosas» and «puso» in his, as he confesses in the prologue, can be detected with Llull’s treatise on chivalry would in fact seem certain. And yet, both as regards the narrative frame, whose plot, after a common start, in Llibre surprisingly stops, while in the Libro it develops up to the predictable epilogue, both for the models of transmission of knowledge proposed, and, above all, for the themes addressed, the differences are more than evident. But in extending the rudiments of scholastic knowledge to chivalric education, don Juan would have suffered the suggestion of another text by Llull: the Llibre de meravelles or Félix, which in offering, according to the encyclopaedic tradition, an exhaustive treatment of the existing, presents an organization of matter similar to that used for the Book. The treatise of Juan Manuel would seem to be configured, therefore, as a sort of condensation, under the same fictional frame, between the two didactic models indicated by Llull, made using contents also taken from other sources, reworked and amalgamated in an original way.